DELAYED PUBERTY AND INSULIN-LIKE GROWTH FACTOR-I IN THALASSEMIA MAJOR AND THALASSEMIA INTERMEDIA ADOLESCENTS: A COMPARATIVE STUDY - Aung, Win-Yu; Htwway, Thae-Nu; Thandar, Myat; Mar, Ohn (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Delayed puberty, a common endocrine complication, is well-recognized in thalassemic adolescents. Evaluation of delayed puberty has been done in both thalassemia major (TM) and thalassemia intermedia (TI) patients but comparative study between them is still limited. Emerging evidence suggests that insulin-like growth factor-I (IGF-I) could have an influence on pubertal development. Therefore, this study aimed to determine and compare delayed puberty and serum IGF-I levels between thalassemic adolescents with different phenotypes. METHODOLOGY A total of 82 thalassemic adolescents (13-17 years), 24 with TM and 57 with TI, attending Day Care Center, Yangon Children Hospital, participated. Delayed puberty was defined as lack of breast development by age of 13, lack of pubic hair by 14, lack of menarche by 16 in female patients and no testicular enlargement by 14, lack of pubic hair by 15 or more in male patients. Fasting serum IGF-I concentrations were determined by ELISA method. RESULTS There was no significant difference in IGF-I concentrations between TM and TI adolescents (P=0.51). Nineteen (79.2%) of TM patients and 52 (91.2%) of TI patients showed delayed puberty. Median IGF-I concentration of TM patients with delayed puberty was significantly lower (P=0.004) than those without whereas, for TI patients, no significant difference (P=0.59) was seen. CONCLUSION A higher percentage of delayed puberty was noted in TI adolescents when compared with TM ones. Circulating IGF-I may play a role in delayed puberty of TM adolescents whereas, in TI adolescents, delayed puberty might not be related to IGF-I level.